If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -8x = 75 Solving 3 + -8x = 75 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -8x = 75 + -3 Combine like terms: 3 + -3 = 0 0 + -8x = 75 + -3 -8x = 75 + -3 Combine like terms: 75 + -3 = 72 -8x = 72 Divide each side by '-8'. x = -9 Simplifying x = -9
| 2k(7k+2)= | | -9-2=3x+5-2x | | (4n+2n^2)+(8n^2+8n)= | | 8x(8x+3)= | | 3b+2.5p=12 | | M=-8/7 | | 9(5-2x)= | | 2x-3(x-5)=5(2x+3) | | 16x+17=9-36x | | 4x+17-3x=-2-11 | | 3x^2-12x+87=0 | | 2x=11-(-1) | | (3x)*(2x+5)=1 | | -7(x+3)-18=23+1 | | 4/52X4/52 | | 2/7y=28 | | (5x+8)*(2x+y)=2 | | 3w-18w=120 | | 6z+2= | | 22x+8-25x=3-7 | | -20+17=m-10 | | 1/9x=28 | | 2/3/x=27.5 | | 2/3x=$27.50 | | (x^2*x)+(2x+y)=5 | | t/25 | | 5x+6(-3.5x+50)=108 | | T-3.5=-1.5 | | 2y=-7x+100 | | P=200+.7*14000 | | 3z^2-3z-1=2z^2-z+3 | | P=200+.3*14000 |